Designing a Mobile-Based Employee Information System Using the Design Thinking Approach - Tiara Arzhety Lubis; Muhammad Dedi Irawan; Dimas Ibnu Muthi (Bigint Computing Journal, 2025)
This research focuses on enhancing workforce management at PT Perkebunan Nusantara IV by implementing a mobile-based personnel information system. The study addresses inefficiencies in manual HR processes, such as delays in task approvals and limited accessibility to employee data. By applying the Design Thinking methodology, the research identifies key challenges, generates solutions, and tests prototypes to develop an intuitive system. The final product improves workflow efficiency and user satisfaction, as demonstrated by usability testing results. Limitations include dependency on internet connectivity and the scope of testing. Future developments could integrate predictive analytics and expand features for comprehensive HR management